Successful prediction of slope failure in an excavation trial. (January 2020) - Botero, E.; Ovando, E.; Mendoza, M.J.
Highlights: Excavation trial. Excavation failure. Soft soils. Soil cracks. Limit equilibrium. Abstract: A new airport for Mexico City was to be constructed some 15 km north of the city at a site in characterized by the existence of very soft, very compressible lacustrine clays that also exhibit very low shear strengths. The construction of the passenger terminal required a rather large excavation that was to be taken down to a depth of 6.5 with slopes having 4:1 gradients. In this paper we describe the general consideration that led the designers to this geometry and to the decision of carrying out a large-scale excavation trial. Simplified limit equilibrium analyses correctly predicted that the excavation would fail before reaching the projected depth. Based on instrumental observations, we give an account of the progress of the excavation until it failed on November 30, 2016, when the excavation reached a depth of 5.0 m below the original ground level. We discuss the events prior to the actual failure, the results of post-failure analyses and the lessons learnt from the results of the excavation trial. Finally, we also discuss the results and validity of sophisticated numerical analyses and of limit analyses performed a priori as well as the results of back calculations.